2018
DOI: 10.1002/cae.21912
|View full text |Cite
|
Sign up to set email alerts
|

Handheld augmented reality system for resistive electric circuits understanding for undergraduate students

Abstract: Augmented Reality (AR) is a recognized technology having a great potential to enhance the cognitive learning process. In this paper, a mobile AR system is proposed which helps in the understanding of resistive electric circuits for undergraduate engineering students. The designed system employs a smartphone, a measuring instrument, and a resistive circuit on a breadboard. The smartphone captures a photograph of the electric circuit and receives data from the measuring instrument (current and voltage) to calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 30 publications
0
23
0
2
Order By: Relevance
“…By effectively organizing and promoting rich environments for STEAM learning, we can immediately and purposefully engage in supporting that outcome (Radziwill et al, 2015). In this context, computer simulations have been proved to be effective in teaching difficult concepts to the students, particularly in the STEAM disciplines (Lindgren et al, 2016;Reyes-Aviles & Aviles-Cruz, 2018). In this respect, Chen and Tsai (2012) contribute stating that although augmented reality technology is not a novelty, its potential in educational applications is currently being explored.…”
Section: Developing and Evaluating Mar Educational Approachesmentioning
confidence: 99%
“…By effectively organizing and promoting rich environments for STEAM learning, we can immediately and purposefully engage in supporting that outcome (Radziwill et al, 2015). In this context, computer simulations have been proved to be effective in teaching difficult concepts to the students, particularly in the STEAM disciplines (Lindgren et al, 2016;Reyes-Aviles & Aviles-Cruz, 2018). In this respect, Chen and Tsai (2012) contribute stating that although augmented reality technology is not a novelty, its potential in educational applications is currently being explored.…”
Section: Developing and Evaluating Mar Educational Approachesmentioning
confidence: 99%
“…Augmented reality (AR) technology is a combination of real and virtual objects which empowers the user to have interaction with 3D graphics in a real scene setting . The research revealed that learning with the AR system has prolonged engagement of the students which results in fun learning and have a positive impression on student learning, motivation, and understanding . Nowadays, the exposure of AR and virtual reality (VR)‐based applications in the education sector is growing at a rapid pace.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the use of augmented reality (AR) to present additional external representations increasingly comes into focus in educational research [ 15 , 16 , 17 , 18 ]. Using AR in laboratory settings thereby enables the integration of virtual information (e.g., measurement data) into the real environment without hindering interaction [ 18 , 19 , 20 ]. This allows formerly invisible phenomena and abstract quantities to become visible (e.g., heat or electricity) as well as visualizing functional relations between real components and virtual visualizations using the spatial and temporal contiguity between them [ 12 , 21 ].…”
Section: Introductionmentioning
confidence: 99%